The Impact of a Company’s Environmental Image on Consumer Purchasing Behaviour - Gunasegaran, Arvinth (2014)
Green marketing is a relatively new field, and there are many opportunities for research especially on developing economies. This comparative study aims to investigate the impact of a company’s environmental image on consumer purchasing behavior in the United Kingdom as opposed to Malaysia. Besides that, it also analyses the level of environmental awareness in these countries and the effect of greenwashing on consumer behavior. The study uses a qualitative-style semi-structured in-depth interview as the data collection method, and employs template analysis as the data analysis technique. Based on the findings, the level of environmental awareness among consumers in the UK is found to be higher than that of Malaysian consumers. Consumers from the UK also have a more positive environmental attitude and tend to buy more green products on average than Malaysian consumers. However, the findings show that most UK and Malaysian participants do not actively look for green products. Finally, it is revealed that the practice of greenwashing is very detrimental to the image of a company and should be avoided. Further to this, some managerial recommendations are also mad